Synthesis and Microbiological Activity of Some Newly Synthesized Derivatives of 2-Oxo-2H-chromen-2-one - Majlinda Daci-Ajvazi; Sevdije Govori; Shuhreta Omeragiq (E-Journal of Chemistry)
By the action of 2-amino-5-methylthio-1,3,4-thiadiazole, 3-amino-5-methylisoxazole, 2-amino-6-fluorobenzothiazole, 2-amino-5-chloropyridine, respectively, on 4-chloro-2-oxo-2H-chromene-3-sulfonyl chloride, the corresponding 9-methylthio-7,7-dioxo-7,7a-dihydro-5-oxo-7λ6,10-dithia-8,11-diaza-cyclopenta[b] phenantren-6-one, 9-methyl-7,7-dioxo-7H-5,8-dioxa-7λ6-thia-7a,11-diaza-cyclopenta[b] phenantren-6-one, 9-fluoro-7,7-dioxo-7H-5-oxa-7λ6,12-dithia-7a,13-diaza-indeno[1,2-b] phenantren-6-one and 9-Chloro-7,7-dioxo-7H-5-oxa-7λ6-thia-7a,12-diaza-benzo[α]anthracen -6-one were formed and they have been isolated in satisfying yields. Based on the biological activity of chromene-2-ones and heterocyclic compounds condensed in position 3 and 4, we also studied microbiological activity of these new compounds (5-8), against Staphylococcus aureus ATCC 25923, Streptococcus pneumoniae, Aeromonas Salmonicida, Bacillus spp and some of them exhibited significant activity.